Crop Sorghum Ensiled With Unsalable Vegetables Increases Silage Microbial Diversity - Forwood, Daniel L.; Hooker, Kristian; Caro, Eleonora; Huo, Yuxin; Holman, Devin B.; Meale, Sarah J.; Chaves, Alex V. (Frontiers in Microbiology, 2019)
Ensiling vegetables with forage crops is a suggested method of waste diversion and can be directly utilized as a livestock feed. Carrot or pumpkin, ensiled at 0%, 20% or 40% dry matter (DM) with crop sorghum, and with or without a second-generation silage inoculant were assessed for nutritive composition, organic acid profiles, aerobic stability and in vitro rumen fermentation characteristics. The study was a completely randomized design, with the fixed effects consisting of vegetable type (carrot vs. pumpkin), level (i.e.: the level of vegetables), inoculant (inoculant or non-inoculant) and the interactions, and mini silos within treatment as the random effect. The experimental unit for sorghum treatments represented by each mini silo (5kg capacity). Silage was sampled after 70-days ensiling for nutrient composition, 14-day aerobic stability, organic acid profiles and microbial diversity. After 24h in vitro incubation, rumen fermentation parameters were assessed, measuring gas and methane (CH4) production, in vitro digestibility and volatile fatty acid concentrations. Sorghum ensiled with carrot or pumpkin at 20% or 40% DM increased crude fat (P≤0.01) and decreased (P≤0.01) silage surface temperature upon aerobic exposure compared to the control. Bacterial communities analyzed through 16S rRNA gene sequencing linearly increased (P≤0.01) in diversity across both vegetables when the vegetable proportion was increased in the silage; dominated by Lactobacillus species. ITS analysis of the fungal microbiota upon silage opening and after 14 d (aerobic stability) identified increased (P≤0.03) fungal diversity with increasing vegetable proportions, predominantly populated by Fusarium denticulatum, Issatchenkia orientalis, Kazachstania humilis and Monascus purpureus. Upon assessment in vitro, there was an increase (P≤0.04) in in vitro digestibility and some CH4 parameters (% CH4, and mg CH4/g DM), with no effect (P≥0.17) on remaining CH4 parameters (mL CH4/g DM, mg CH4/g digested DM), gas production or pH. However, increasing vegetable amount decreased percentage of acetic acid and increased percentage of propionic acid of the total VFA, decreasing A:P ratio and total VFA concentration as a result (P≤0.01). The results from this study indicate including carrot or pumpkin at 20% or 40% DM in a sorghum silage can produce a highly digestible, microbially diverse and energy-rich livestock feed.